Synthesis of oxygenated additive fuels from bio-renewable glycerol using sulfated Zr-Al based heterogeneous acid catalyst - Maurya S.; Sharma Y.C. (My University, 2025)
The exponential growth of biodiesel production generates an enormous amount of glycerol as a by-product that requires effective strategies to convert it into valuable chemicals to enhance the sustainability of the biodiesel market. Solketal is an interesting compound among various value-added chemicals obtained from waste glycerol produced during biodiesel production. In the present work, highly efficient and economically viable heterogeneous solid acid SO4-2/ZrO2-Al2O3 catalyst was designed via wetness impregnation process. The synthesized catalyst was found to be highly active for acetalization of glycerol with acetone under optimized conditions viz. 1:10 M ratio of glycerol and acetone, 3 wt.% of catalyst loading at 70 °C for 180 min reaction time. The synthesized catalyst is highly selective (98.9%) for solketal synthesis, with 98.1 % yield and 99.2 % glycerol conversion. Green metrics studies were performed to determine the environment-friendly nature of the catalyst and acetalization process. The carbon balance studies were also calculated to show that glycerol is found only in one phase during the overall process of solketal synthesis. The high thermal stability and catalytic activity were retained up to 5th reaction cycle making the catalyst more efficient for its wide application in an industrial level. © 2023 Elsevier Ltd